Impact of COVID-19 pandemic on the Nigeria stock market: A sectoral stock prices analysis - Yakubu A. Bello; Peter A. Adekunle; Udochukwu G. Nwachukwu (CBN Journal of Applied Statistics, 2022)
This study examines the impact of the COVID-19 pandemic on sectoral stock prices in Nigeria stock market using daily data covering from February 28, 2020 to June 26, 2020. Applying the autoregressive distributed lag (ARDL) bounds test, the study finds that COVID-19 pandemic had adverse impact on the stock market indices in the short run. Furthermore, the study documents negative response of sectoral stock prices to the pandemic while the stock prices of the banking sub-sector are the worst hit. Compared to the consumer goods, and industrial subsector indices, the speed of adjustment to long run equilibrium is faster for the banking, subsector. Results from sensitivity analysis also indicate that the stock market responds negatively to the pan- demic when the number of confirmed COVID-19 deaths is used. However, the stock market performance is more sensitive to the total number of confirmed cases than the total number of confirmed deaths. This implies that the market responds quickly to the pandemic. This paper, therefore, concludes that the COVID-19 pandemic had negative and heterogenous impacts on sectoral stock prices in Nigeria during the first wave of the pandemic.
Keywords: C22; F32; I15; O55; 330; COVID-19; stock market; Nigeria; bounds test; sectoral stock prices